Identification of telomere maintenance gene variations related to lung adenocarcinoma risk by genome‐wide association and whole genome sequencing analyses - Shiraishi, Kouya; Takahashi, Atsushi; Momozawa, Yukihide; Daigo, Yataro; Kaneko, Syuzo; Kawaguchi, Takahisa; Kunitoh, Hideo; Matsumoto, Shingo; Horinouchi, Hidehito; Goto, Akiteru; Honda, Takayuki; Shimizu, Kimihiro; et al. (Cancer communications (London, England), 2024)
List of abbreviations GWAS genome-wide association studies LADC lung adenocarcinoma WGS whole genome sequencing SNP single nucleotide polymorphism EGFR epidermal growth factor receptor TERT telomerase reverse transcriptase TP63 tumor protein p63 TERC telomerase RNA component POT1 protection of telomeres 1 PTPRG protein tyrosine phosphatase receptor type G BTN2A1 butyrophilin subfamily 2 member A1 HLA-C major histocompatibility complex, class I, C HLA-DQB1 major histocompatibility complex, class II, DQ beta 1 BAK1 BCL2 antagonist/killer 1 ASB15 ankyrin repeat and SOCS box containing 15 SECISBP2L SECIS binding protein 2 like TERF1 telomeric repeat binding factor 1 TINF2 TERF1 interacting nuclear factor 2 OBFC1 OB-fold-containing 1 TRF1 telomeric repeat binding factor 1 RAP1 TERF2 interacting protein LTL leukocyte telomere length Dear editor, Lung carcinoma is responsible for the highest fatality rate among cancer-related deaths globally, with lung adenocarcinoma (LADC) emerging as the prevailing subtype. [...]it is plausible that risk factors exerting a more pronounced influence in Asian than in European/American populations contribute to LADC pathogenesis, irrespective of smoking status. [...]despite genetic disparities between Caucasian and Asian populations, the populations share genetic factors contributing to lung carcinoma susceptibility. Abbreviations: EGFR, epithelial growth factor receptor; Ctrl, control; KGP p3, 1000 genomes project phase 3; RSQR, imputation quality; LADC, lung adenocarcinoma; LTL, leukocyte telomere length; TERC, telomerase RNA component; TERT, telomerase reverse transcriptase; POT1, protection of telomeres 1; TL, telomere length; SNP, single nucleotide polymorphism; TINF2, TERF1 interacting nuclear factor 2; OBFC1, OB-fold-containing 1.